A PATHOLOGIST HITCHHIKER'S GUIDE TO INFORMATICS. (February 2015) - Legg, Michael; Bott, Lawrence; Edwards, Glenn; Ellis, David; Sikaris, Ken
Abstract : The contemporary practice of pathology is heavily reliant upon information systems. These systems are becoming increasingly sophisticated and College Fellows are frequently required to have input on their design, selection, implementation and evaluation. Laboratories are adopting decision support technologies to support workflow management and clinical interpretation of pathology tests. The computationally intensive field of bioinformatics is growing rapidly especially in genomics laboratories while statistics, another informatics discipline, has always been an important part of Fellowship training. College Fellows have a professional duty of care, and also carry ethical and medico-legal responsibility, for the efficacy, reliability, safety and security of such systems. Significantly, the development of Health Informatics also proceeds apace in the wider medical community. Data mining tools, social media and decision support are expected to improve health resource utilisation, evidence-based practice, and clinical effectiveness. These tools will also become widely deployed as patients and health consumers have more control over health service delivery and expect an improved experience in their contact with the health system.